2017
DOI: 10.1016/j.coph.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Muscle as a paracrine and endocrine organ

Abstract: Skeletal muscle cells are highly abundant and metabolically active and are known to ‘communicate’ their energy demands to other organs through active secretion. Muscle-derived secretory proteins include a variety of cytokines and peptides collectively referred to as “myokines” that exert auto-, para- or endocrine effects. Analyses of the skeletal muscle secretome revealed that numerous myokines are secreted in response to contraction or strength training, and that these factors not only regulate energy demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
186
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(206 citation statements)
references
References 54 publications
2
186
0
7
Order By: Relevance
“…It is well documented that skeletal muscle has many physiological functions through biomechanical stress and multiple myokines . Studies have shown high muscle mass reduces the risk of osteoporosis and contributes to cardiovascular health in adults .…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that skeletal muscle has many physiological functions through biomechanical stress and multiple myokines . Studies have shown high muscle mass reduces the risk of osteoporosis and contributes to cardiovascular health in adults .…”
Section: Discussionmentioning
confidence: 99%
“…29 PGC1α is induced by oxidative stress, is a powerful regulator of reactive oxygen species (ROS) removal by increasing the expression of numerous ROSdetoxifying enzymes and factors such as NF-E2-related factor 2 (Nrf2), 30 and is directly regulated by the transcription factor Tfe3 in muscles 31 ( Figure 2). [58][59][60][61][62][63] Myokines exert autocrine, paracrine, or endocrine effects, thereby not only regulating energy demand but also contributing to the broad beneficial effects of exercise on cardiovascular, metabolic, and mental health. 35 Thus, altered PGC1α expression level/activity in muscle tissue likely consequent to age-related enhanced ROS production in a background of altered mitochondria number and properties 36,37 might concur to sarcopenia.…”
Section: Altered Myofiber Metabolismmentioning
confidence: 99%
“…By inducing a moderate level of oxidative stress, physical exercise up-regulates PGC1α essential for mitochondriogenesis promoting oxidative fibre formation at the expense of glycolytic fibre formation, 32 improving exercise performance, 33 increasing muscle mass and strength and resistance to muscle wasting, 34 and augmenting early steps in the activation and proliferation of adult muscle stem cells. 62 Among the various myokines, interleukin (IL)-15 stimulates myofiber hypertrophy, IL-8 stimulates angiogenesis, IL-6 stimulates glucose uptake and fatty acid oxidation, and decorin binds to and blocks myostatin, another myokine, thus preventing myostatin's inhibitory effects on muscle trophism. Physical exercise and caloric restriction exert trophic/protective effects on skeletal muscles via several mechanisms.…”
Section: Altered Myofiber Metabolismmentioning
confidence: 99%
“…They are released into circulation and exert a variety of systemic effects promoting crosstalk among different tissues [1]. Irisin is known to retrieve disuseinduced bone loss by stimulating the osteoblast pathways, while myostatin was demonstrated to be highly expressed in the synovial tissues of rheumatoid arthritis (RA) subjects, with direct role in osteoclastogenesis [2,3].…”
mentioning
confidence: 99%
“…Inflammation and autoantibodies indipendently promote endothelial dysfunction, which is the earliest, reversible stage of atherosclerosis. In vitro studies have demonstrated that antibodies against carbamylated proteins (anti-CarP), recently described in RA patients, can induce the production of proatherosclerotic molecules like Vascular Cell Adhesion Molecule (VCAM-1) and activate Interleukin-1 Receptor-Associated Kinase (IRAK-1), Nuclear Factor kB (NF-kB), inducible Nitric Oxide Synthase (iNOS) in endothelial cells(1,2). Moreover, anti-CarP are associated to endothelial dysfunction and subclinical atherosclerosis in RA patients(3).…”
mentioning
confidence: 99%